Mathematics classes for tourism undergraduate students and pre-service teachers with active methodologies using technologies - Santos, Vanda (2022)
In the last few decades, technology has advanced in multiple fields, including Education. Some of its benefits include improving student performance and motivation, fostering active learning and tracking student progress. Game-based learning platforms, like Kahoot!, can be used for reviewing content and motivating students for learning. The participants in the study are undergraduate and post-graduate students from two Portuguese public higher education institutions. The aim of the study is to investigate students’ perceptions of how Kahoot! can be used as a tool for reviewing class content or designing warm-up activities. A quantitative survey is being conducted to gather information about students’ insights on the use of Kahoot!. Other studies have also shown that higher education students are usually receptive to the use of this tool, finding it useful to increase their motivation and considering that technology can positively impact learning.